Cardiocerebrovascular benefits of early rhythm control in patients with atrial fibrillation detected after stroke: a systematic review and meta-analysis - Ma, Liang; Wang, Baofu; Fan, Jiasai; Zhou, Hufang; Li, Jingen; Li, Weisheng; Zheng, Xiangying; Wang, Xian (Frontiers in Cardiovascular Medicine, 2024)
Objective: This study aimed to evaluate the impact of Early Rhythm Control (ERC) on the occurrence of cardiocerebrovascular events in patients diagnosed with Atrial Fibrillation Detected After Stroke (AFDAS).Methods: A systematic search was conducted across nine databases from inception to October 15, 2023, to identify clinical trials comparing ERC with usual care interventions in AFDAS patients. The primary outcome assessed was recurrent stroke, with secondary outcomes including all-cause mortality, adverse events related to arrhythmias, and dementia. Results: Analysis of 5 studies, consisting of 2 randomized clinical trials (RCTs) involving 490 patients and 3 cohort studies with 95,019 patients, revealed a reduced rate of recurrent stroke (OR=0.30, 95%CI 0.11-0.80, P=0.016 in RCTs; OR=0.64, 95%CI 0.61-0.68, P<0.00001 in cohort studies) and all-cause mortality (HR=0.94, 95%CI 0.90-0.98, P=0.005 in cohort studies) in the ERC group compared to usual care. Additionally, ERC was associated with superior outcomes in terms of dementia.Patients with AFDAS who underwent ERC treatment exhibited a decreased risk of cardiocerebrovascular events compared to those receiving usual care.These results support the potential benefits of implementing an ERC strategy for this specific patient population.